The Effectiveness of Halte to Just - I Wayan Arnaya; Ilham Ramadhan (Pusat Penelitian dan Pengabdian Masyarakat Poltrada Bali, 2020)
Bus stops or shelters are places for boarding and boarding passengers, usually placed on the bus service network. In the center of the city is placed at a distance of 300 to 500 m and in the suburbs between 500 to 1000 m.Between other functions of the bus stop into a means of transit for a journey, allowing passengers to find a means of transportation to a destination. The existence of this bus stop compares the smooth traffic and congestion points in the city of Semarang.